RECOMMENDATIONS FOR DIAGNOSTICS AND TREATMENT OF NIEMANN-PICK TYPE C DISEASE - James E. Wraith; Matthias R. Baumgartner; Bruno Bembi; Athanasios Covanis; Thierry Levade; Eugen Mengel; Merce Pineda; Frederic Sedel; Meral Topcu; Marie T. Vanier; Hakan Widner; Frits A. Wijburg; et al. (Union of pediatricians of Russia, 2010)
(Pediatric Pharmacology. - 2010; 7(1):16-24)